2022
DOI: 10.1111/vsu.13873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified radiographic union scale for tibial fractures scoring system in staged bilateral tibial plateau leveling osteotomy procedures and comparison of first and second side radiographic bone healing

Abstract: Objective To evaluate the inter‐ and intra‐rater reliability of the tibial plateau leveling osteotomy (TPLO) modified radiographic union scale for tibial fractures (mRUST), a semiquantitative scoring system, as compared with the subjective evaluation of radiographic union for staged TPLOs. Study design Retrospective study. Animals Forty‐eight dogs, 96 stifles. Methods Medical records were reviewed for dogs with bilateral cranial cruciate ligament injuries diagnosed at presentation that underwent staged bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…29,30 The modified RUST system was used by Walker and colleagues to evaluate bone healing in dogs that underwent TPLO, and it was determined to have higher interobserver reliability when compared with a subjective evaluation of radiographic union (i.e., Yes/No). 19 The need for a standardized radiographic scoring system for assessment of bone healing after TPLO warrants further prospective investigation comparing the modified RUST, Visual Analogue Score, and the 10-point scoring systems to determine intraand interobserver reliability. A standardized scoring system could also provide future application in the evaluation of the healing of different osteotomies and fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 The modified RUST system was used by Walker and colleagues to evaluate bone healing in dogs that underwent TPLO, and it was determined to have higher interobserver reliability when compared with a subjective evaluation of radiographic union (i.e., Yes/No). 19 The need for a standardized radiographic scoring system for assessment of bone healing after TPLO warrants further prospective investigation comparing the modified RUST, Visual Analogue Score, and the 10-point scoring systems to determine intraand interobserver reliability. A standardized scoring system could also provide future application in the evaluation of the healing of different osteotomies and fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Osteotomy healing following TPLO has been evaluated in multiple studies, and a 5-point (0-4) scoring system evaluating osseous bridging is commonly utilized. [14][15][16][17][18][19][20] A 10-point (0-10) scoring system was later developed, specifically for evaluation of bone remodelling at the osteotomy site in standard TPLO radiographs and although it appeared to provide a more sensitive evaluation of osteotomy healing, inter-and intraobserver variability were not evaluated in this study. 18 Other scoring systems have been used and compared; however, there is currently no standardized scoring system for the evaluation of osteotomy healing in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown the VAS system to be useful in identifying subtle bone healing by looking at healing over a 2-week interval. In comparison, Walker et al evaluated the modified radiograph union scale for tibial fractures (mRUST) system compared to the subjective evaluation of radiographic osteotomy union utilizing radiographs taken at an average of 8.4 weeks postoperative ( 11 ). The mRUST system is similar to the DESCRIPTOR system in terms of specifically evaluating the cortical margins although it does not allow for the same completeness ratings ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a common and fairly standardized osteotomy with internal fixation for management of CCLD, TPLO patients may pose a useful clinical model to investigate variables that affect osteotomy healing ( 1 , 8 , 9 ). Various methods that evaluate radiographic TPLO osteotomy healing have been described, including different variations of 5-, 10-, and 12-point scales, however, there is no agreed upon grading standard ( 8 11 ). With many different grading scales, there are bound to be variations in degree of healing reported due to the grading methodologies.…”
Section: Introductionmentioning
confidence: 99%